Transformasi Arbitrase Berbasis Online Dispute Resolution (ODR) : Praktik Global dan Implikasi Hukumnya di Indonesia - Hanin Muna Saniyyah (CV. Denasya Smart Publisher, 2026)
The development of information technology has transformed dispute resolution mechanisms, including arbitration, through the implementation of Online Dispute Resolution (ODR). ODR is an evolution of Alternative Dispute Resolution (ADR) that utilizes information and communication technologies to resolve disputes electronically without requiring the physical presence of the parties. This article aims to analyze the development of ODR in global arbitration practices and examine how Indonesia's legal framework accommodates its implementation. This study employs a normative juridical method using statutory and library research approaches. The findings indicate that ODR has developed into an efficient dispute resolution mechanism, particularly for cross-border business disputes, due to its accessibility, cost efficiency, and faster procedures. This development is reflected in the case of Nexcess.net, LLC v. Md. Asaduzzaman, which was resolved entirely online through the WIPO Arbitration and Mediation Center. In Indonesia, the legal basis for ODR can be found in Law Number 30 of 1999, the Electronic Information and Transactions Law, Government Regulation Number 80 of 2019, and BANI regulations concerning electronic arbitration. However, the absence of a comprehensive regulation specifically governing ODR may create legal uncertainty. Therefore, more specific regulations are required to strengthen the effectiveness of digital dispute resolution in Indonesia.